Religiusitas sebagai Moderasi dan Faktor yang Mempengaruhi Niat Wisatawan Mengunjungi Wisata Halal di Indonesia - Sulistyo Budi Utomo; Reza Nurul Ichsan; Tribowo Rachmat Fauzan; Luckhy Natalia Anastasye Lotte; Muh. Zakaria (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Halal tourism has become an industry that has a positive impact in both Muslim majority and minority countries. If previously this industry seemed exclusive because it was limited by something called 'haram', then halal tourism has become an attractive option because it is an activity without having to sacrifice religion by touching on 'haram' elements. This research aims to determine the influence of religiosity as a moderation and factor that influences tourists' intentions to visit halal tourism in Indonesia. The current analysis uses a quantitative approach. The results of this research have found that attitude, subjective norms and perceived behavioral control influence tourists' intentions to visit halal tourism in Indonesia. Religiosity as moderation is able to moderate subjective norms regarding tourists' intentions to visit halal tourism in Indonesia. However, religiosity was not able to moderate attitude and perceived behavioral control on tourists' intentions to visit halal tourism in Indonesia in this study.